The Accessibility of the Late Medieval Goldsmith Guild of Bruges - Muylaert, Silke (TSEG - The Low Countries Journal of Social and Economic History, 2019)
The aim of this article is twofold. First, it offers an analysis of heredity and exclusivity in Bruges' late medieval goldsmith guild on the basis of prosopographical research. It examines family ties and the entrance of newcomers to this guild, thereby also exposing the flexibility of guild regulations. In second place, it focuses on the relationship between the perceived exclusivity of goldsmith guilds and the functioning of this guild in practice. In doing so, this article becomes a case study demonstrating the place of goldsmith guilds in debates concerning the nature of guilds.